Subskills associated with spelling ability in children with and without autism spectrum disorders. (October 2018) - Bailey, Benjamin; Arciuli, Joanne
Background and aims: Effective literacy instruction demands a clear understanding of the subskills that underpin children's reading and writing abilities. Some previous research on reading has questioned whether the same subskills support literacy acquisition for typically developing children and children with autism spectrum disorders. This study examined the subskills associated with spelling ability in a group of 20 children with ASD aged 5–12 years (ASD group). A group of 20 typically developing children matched for age and word spelling accuracy (TD group) provided comparative data. Methods: Participants completed standardised assessments of vocabulary, phonological awareness, letter knowledge and word spelling. Errors produced in response to the word spelling assessment were analysed for evidence of phonological awareness. In addition, all spelling attempts were analysed for evidence of phonological, orthographic, and morphological awareness, 'linguistic awareness', using the Computerised Spelling Sensitivity System. Results: Correlation and regression analyses showed statistically significant relationships between phonological awareness and word spelling accuracy for children in the ASD and TD groups. Spelling errors produced by both groups contained evidence of phonological awareness. Analysis of all spelling attempts showed that the overall level of linguistic awareness encoded by children in the ASD and TD groups was not significantly different. Conclusions: These findings provide evidence that phonological awareness and other subskills support spelling in children with autism spectrum disorders as they do in typically developing children. Implications: The similar spelling profiles exhibited by children with autism spectrum disorders and their typically developing peers suggest that these populations may benefit from literacy instruction that targets the same underpinning subskills.